Peran Kartografi dalam Menyajikan Informasi Geografis - Muhammad Iqra Fahren (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Cartography is a field that combines science and art in the creation of maps to present geographical information in a visual format. In this regard, cartography plays a vital role in simplifying complex and abstract geographical data, making it easier to understand and use. Maps allow for the representation of geographical phenomena through symbols, colors, and other visual elements, which facilitate analysis and decision-making. Furthermore, technological advancements, such as Geographic Information Systems (GIS) and satellite- based digital mapping, have enhanced cartography's ability to provide more accurate and dynamic data. This article discusses the role of cartography in presenting geographical data by highlighting visualization techniques, the use of the latest technologies, and its practical applications across various sectors. Therefore, cartography is not just a tool for creating maps but also an essential means of analyzing and understanding more complex geographical data.